Association of Abnormal Serum Bilirubin and Liver enzymes in Iraqi Patients with Metabolic Syndrome (A cross-sectional study) - Duaa Hussein Ali; Rawaa Hadi Shareef (مجلة الكوفة الطبية)
Background: Metabolic syndrome affects people worldwide. Hypertension, insulin resistance, central obesity, dyslipidemia, and pro-inflammatory state are cardiometabolic risk factors. Bilirubin is produced from the breakdown of haemoglobin. Recent studies show that small bilirubin elevations can protect tissue and control oxidative stress and inflammation. Alanine aminotransferase (ALT) is primarily located in the liver but also in the heart, kidneys, and muscles. Aspartate aminotransferase (AST) is present in the liver, kidneys, skeletal and cardiac muscles, and brain. Objectives: The study aims to assess the impact of bilirubin and liver enzymes on the components and severity of metabolic syndrome(Obesity, fasting blood glucose, Triglycerides, HDL, and blood pressure). Materials and methods: This cross-sectional study was conducted at the diabetes center in Al-Najaf City, Iraq, from October 2023 to February 2024. Age, gender, blood pressure, height, weight, fasting blood glucose, bilirubin, ALT&AST, triglycerides, and HDL were examined in 122 Mets patients. Results: The study results show a significant difference (P<0.05) in the levels of bilirubin(0.9280±0.03783), ALT(12.8934±0.40234), and AST (22.0410 ± 0.89667) among individuals with metabolic syndrome. Also, the study found a significant difference in ALT levels between overweight (19.8409±1.17134), obese (24.0192±.96722), and normal BMI persons (13.7692±.84909). A significant difference in AST levels was observed between those with normal BMI (16.0000±1.29970) and those with overweight (21.3182±1.72740) or obesity (22.4615±.93791). Between BMI groups, bilirubin levels were not substantially different. The study found a positive correlation between ALT and AST with fasting blood glucose and triglyceride. Conclusion: Metabolic syndrome patients have greater liver enzyme levels than others, which increases insulin resistance and oxidative stress, increasing MS risk. Furthermore, liver aminotransferases have the potential to induce diabetes. Furthermore, increased triglyceride levels led to the release of greater hepatic enzyme concentrations; however, total bilirubin and MS do not correlate.